Pengaruh Pakan Egg Custard terhadap Laju Pertumbuhan Benih Ikan Lele Lokal (Clarias batrachus) - Octoriani, Widyanti; Rahmawati, Fatihah Hani; Hafid, Dzakiyatul Fikriyah; Alfiah, Lianni Nur; Fahardico, Rizky (Universitas Batangahari Jambi, 2026)
Catfish (Clarias batrachus) is an important aquaculture commodity in Indonesia due to its rapid growth and high market demand. Feed plays a crucial role in determining the growth and survival of fry; therefore, alternative feeds that are nutritious and cost-effective, such as egg custard, are needed. This study aimed to evaluate the effects of egg custard and Artemia feed on the growth performance and survival rate of catfish fry. The experiment consisted of two treatments, namely egg custard and Artemia. Parameters observed included daily growth rate, absolute weight gain, feed conversion ratio (FCR), and survival rate (SR). Data were analyzed descriptively and supported by statistical analysis. The results showed that egg custard resulted in higher daily growth rate and absolute weight gain, as well as better survival rate compared to Artemia. However, the FCR value of egg custard was higher, indicating lower feed efficiency. Therefore, egg custard has potential as an alternative feed to enhance growth and survival of catfish fry, but further optimization is required to improve feed efficiency